Rapid and simple CZE-UV method for quality control of B1 and B6 vitamins in drugs and dietary supplements - Matuskova M.; Cizmarova I.; Chalova P.; Mikus P.; Piestansky J. (Sciendo, 2021)
The application of hydrodynamically closed capillary zone electrophoresis combined with convenient ultraviolet (UV) detection allows fast, simple, environmentally friendly and cost-effective analysis of ions or ionisable molecules. This technique has been used to determine two selected B vitamins (thiamine, pyridoxine) in various drug formulations. The developed method was characterised by excellent validation parameters, such as linearity, precision, accuracy, limit of detection and limit of quantification. The total time of analysis was lower than 13.5 min. The results indicate that the method is suitable for implementation in routine quality control of selected B vitamins in pharmaceutical and food samples.